مشكلة تعلّم الصرف العربي، أسباب وحلول: الإعلال والإبدال أنموذجاً = Difficulties of learning Arabic morphology, reasons and solutions, í’lãl and ibdãl as an example - Md. Noor, Mohamad Lukman Al Hakim; Sahrir, Muhammad Sabri (Pusat Pengajian Teras (PPT), KUIS, 2019)
This study deals with the issue of learning Arabic morphology by using multimedia via the World Wide Web as it seeks to help students to learn through the design of a computer-assisted program. Among the objectives of this study are to know difficulties faced by many non-native Arabic language learners in learning Arabic morphology, and to know learners’ perception of learning Arabic morphology by using the multimedia. This study adopted both descriptive and analytical methodologies. The researcher collected information about the difficulties in learning Arabic morphology and the learning theories of Arabic language via the World Wide Web. In addition, there were three stages of academic procedures in the analytical approach. Firstly, learner’s needs analysis which was completed before the design phase. Secondly, expert review which was conducted during the design phase. The third stage was the analysis of formative evaluation and pre- and post-test after the completion of the development phase. Through the result of the needs analysis, the researcher managed to identify the difficulties in teaching and learning Arabic morphology and the survey show that ílãl and Ibdãl scored the highest difficulties in learning Arabic Morphology. Then, the researcher designed a computer-assisted program by using multimedia via the URL of http://efolio.iium.edu.my/courses/sorof/index.html through Blendspace website. It was developed in light of instructional design model of ADDIE based on the respondents’ views, suggestions and needs. The researcher found that this multimedia learning programme is highly accepted by the respondents based on their pre- and post-tests’ result that shows a statistically significant difference between both tests, as it leads to a productive and successful process of learning Arabic morphology as a second language, as well as implementing it in other disciplines of Arabic as a second language. ************************************************************************************* تتناول هذه الدراسة قضية تعلم الصرف العربي باستخدام الوسائط المتعددة عبر الشبكة العالمية التي تساعد الدارسين في تعلمه. ومن أهداف هذا البحث هي الكشف عن الصعوبات التي يواجهها الطلبة في دراسة الصرف. وبناءً على نتائج تحليل الحاجات، استخلص الباحث عدة صعوبات في تعلم الصرف العربي التي تعود إلى المعلم وطبيعة المادة نفسها. ثم صمّم بعد ذلك الوحدات الحاسوبية الصرفية في تعلم الإعلال والإبدال مستخدمًا الوسائط المتعددة على ضوء نموذج أدي (ADDIE) وتم عرضها عبر موقع بلندسفاس (Blendspace). وقد تمّ تطبيقها على عينة الدراسة التي تتكون من الدراسين المتخصصين في اللغة العربية في الجامعة الإسلامية العالمية بماليزيا. وكشف الباحث أن ما تمّ تصميمه ناجحٌ وحث الباحث إلى تطوير هذا النموذج وتطبيقه على فروع مختلفة في اللغة العربية بوصفها لغةً ثانيةً.